Analysis of Communication Effectiveness on Parking Stand Arrangements by the Apron Movement Control (AMC) Unit and Air Traffic Controller (ATC) of Halim Perdanakusuma International Airport - Yuniar Istiyani; Liza Amalia (Journal of Education Technology Information Social Sciences and Health, 2024)
Halim Perdanakusuma International Airport has the task of maintaining facilities. The airside area is one of the facilities that must be considered. The unit responsible for flight operations while on the airside is the Apron Movement Control (AMC) unit. Efforts made by the AMC unit so that flight activities run smoothly are communicating effectively with the Air Traffic Controller (ATC) unit when determining the location of the aircraft parking stand. However, the AMC and ATC units of Halim Perdanakusuma International Airport often find obstacles in conducting effective communication. This study aims to analyze the effectiveness of communication towards parking stand arrangements by AMC and ATC units at Halim Perdanakusuma International Airport. This research method uses qualitative methods based on observation, interviews and documentation, and is presented in descriptive form. The research was conducted with 5 resource persons in charge of the Apron Movement Control (AMC) and Air Traffic Controller (ATC) units at Halim Perdanakusuma International Airport. Based on the results of interviews, observations and research conducted directly by the author, it shows that the effectiveness of communication carried out by the Apron Movement Control (AMC) and Air Traffic Controller (ATC) units regarding the location of parking stands at Halim Perdanakusuma International Airport has not been effective due to frequent obstacles in communication caused by sudden schedule changes and inadequate communication tools.